2010
DOI: 10.1111/j.1440-1797.2009.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological features of renal amyloidosis: An analysis of 32 patients in a single Chinese centre

Abstract: Renal amyloidosis is frequently neglected by local physicians in China. Middle-aged nephrotic patients with weight loss, organ enlargement and monoclonal light chains in serum or urine should be highly suspected of the disease. Renal biopsies, especially electron microscopy, play a crucial role in the early diagnosis of renal amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Inconsistent data on renal size in amyloidosis were reported (10,19,20). We found that the kidney size did not vary significantly among different stages of CKD (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent data on renal size in amyloidosis were reported (10,19,20). We found that the kidney size did not vary significantly among different stages of CKD (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 gas condensed into liquid in the corresponding saturation temperature ( generally between -35℃ and -25℃), then was stored in the storage tank. The method was improved on the basis of high pressure process, decompression to low pressure with desulphurization, drying and high pressure throttle [7] , cooled by ammonia. The process separated many impurities with the similar boiling point to CO 2 , the purity of the product were greatly improved.…”
Section: Low-pressure Cryogenic Methodsmentioning
confidence: 99%
“…Other examples include the long-term hemodialysis, amyloid transthyretin in senile systemic amyloidosis, and beta 2 microglobulin in hereditary polyneuropathies. 1,3 The majority of hereditary amyloidosis cases are linked to inherited inflammatory conditions such familial Mediterranean fever (FMF). The morbidity of amyloidosis is influenced by the organs implicated, their level of functional compromise, and the amyloid fibrils' direct toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to score the renal amyloid deposits. 1,3,4 Sen et al scored renal amyloidosis by grading system which offers a superior tool for comparing and predicting the therapeutic outcomes. 4 It is essential to score amyloid deposits using the standardized criteria in order to evaluate the disease progression and to promote uniformity and interinstitutional comparison of reports.…”
Section: Introductionmentioning
confidence: 99%